Analyzing factors influencing customer satisfaction on purchased cybersecurity solutions within B2B organizations in Malaysia - Subramaniam, Nageswar Rao (2024)
This research is about customer satisfaction with the cybersecurity solutions purchased among B2B (Business-to-Business) organizations in Malaysia which aims to explore how the effect of service quality perception influences customer satisfaction which subsequently impacts word-of-mouth (WOM) and repurchase intentions. In an ever-evolving cybersecurity threat landscape, cybersecurity solutions play a critical role in protecting sensitive data to ensure a secure operating environment for businesses. However, there is lack of comprehension regarding the measures that influence customer satisfaction among B2B organizations in Malaysia towards the purchased cybersecurity solutions. This research employed a self-administrated questionnaire to collect data from a total of 273 respondents within B2B organizations across various industries in Malaysia. The data were analyzed in various aspects of service quality and customer satisfaction using SPSS and SmartPLS in presenting the results finding. The study results indicate that all the six constructs tested within the model have positive and significant impact except for perceived technical quality. Therefore, this study and proposed conceptual framework will be extremely valuable for cybersecurity solution providers in guiding them to provide cybersecurity solutions that able to enhance customer satisfaction among B2B organizations. Furthermore, the findings of this result will also pave way for a similar study being conducted in the future.